2019
DOI: 10.1155/2019/1694695
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Lower Extremity Neuromuscular Control Exercises on Knee Proprioception, Muscle Strength, and Functional Level in Patients with ACL Reconstruction

Abstract: Objective The purpose of this study was to determine the effects of lower extremity motor control exercises on knee proprioception, muscle strength, and functional level in patients with anterior cruciate ligament reconstruction (ACL-R). Materials and Methods Thirty-two of the 57 patients with ACL-R using tibialis anterior allografts were divided into two groups. Group I: lower extremity motor control exercises were added to the standard rehabilitation program. Group II: standard rehabilitation program was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 24 publications
2
63
0
9
Order By: Relevance
“…Proprioceptive training included balance training, agility drills, wall squats and stability exercises. Most included participants went through reconstruction surgery with autologous tendon 11,16,17,22–34 except 1 study 21 with allogeneic tendon reconstruction. Five studies 17,24,26–28 reported meniscus injuries and performed meniscus repair surgery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Proprioceptive training included balance training, agility drills, wall squats and stability exercises. Most included participants went through reconstruction surgery with autologous tendon 11,16,17,22–34 except 1 study 21 with allogeneic tendon reconstruction. Five studies 17,24,26–28 reported meniscus injuries and performed meniscus repair surgery.…”
Section: Resultsmentioning
confidence: 99%
“…16,17,21,33,34 two studies reported the loss to follow-up. 17,21 In addition, the results of methodological quality assessment using improved Jadad score were presented in Table 1. Five high-quality studies 16,17,21,33,34 with Jadad score ⩾ 4 and 12 low-quality studies 11,22–32 with Jadad score ⩽ 3 were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the standardized warm-up, the MVC tests for the knee extensors, knee flexors, and plantar flexors of the dominant leg were performed on an isokinetic dynamometer (CON-TREX ® Multijont, Duebendorf, Switzerland). For the knee extensor MVC, the participant was seated on the dynamometer with both hip and knee angles of 110° ([ 12 ]; 180° = anatomical zero [ 13 ]). For the knee flexor MVC, the participant was positioned supine on the dynamometer with hip and knee angles of 90° and 110°, respectively.…”
Section: Methodsmentioning
confidence: 99%